Nijmegen breakage syndrome (NBS) with neurological abnormalities and without chromosomal instability. Issue 3 (20th July 2005) - Seemanová, E; Sperling, K; Neitzel, H; Varon, R; Hadac, J; Butova, O; Schröck, E; Seeman, P; Digweed, M
Abstract : Background: Nijmegen breakage syndrome (NBS) is an autosomal recessive chromosomal instability disorder with hypersensitivity to ionising radiation. The clinical phenotype is characterised by congenital microcephaly, mild dysmorphic facial appearance, growth retardation, immunodeficiency, and greatly increased risk for lymphoreticular malignancy. Most NBS patients are of Slavic origin and homozygous for the founder mutation 657del5. The frequency of 657del5 heterozygotes in the Czech population is 1:150. Recently, another NBS1 mutation, 643C>T(R215W), with uncertain pathogenicity was found to have higher frequency among tumour patients of Slavic origin than in controls. This alteration results in the substitution of the basic amino acid arginine with the non-polar tryptophan and thus could potentially interfere with the function of the NBS1 protein, nibrin. Methods and Results: Children with congenital microcephaly are routinely tested for the 657del5 mutation in the Czech and Slovak Republics. Here, we describe for the first time a severe form of NBS without chromosomal instability in monozygotic twin brothers with profound congenital microcephaly and developmental delay who are compound heterozygotes for the 657del5 and 643C>T(R215W) NBS1 mutations. Both children showed reduced expression of full length nibrin when compared with a control and a heterozygote for the 657del5 mutation. Radiation response processes such as phosphorylation of ATM and phosphorylation/stabilisation of p53, which are promoted by NBS1, are strongly reduced in cells from these patients. Conclusions: Interestingly, the patients are more severely affected than classical NBS patients. Consequently, we postulate that homozygosity for the 643C>T(R215W) mutation will also lead to a, possibly very, severe disease phenotype.